The electoral effect of pork barrel politics: evidence from England - Johannes Lattmann (Public Choice, 2024)
This study examines the effect of the allocation of centralised funding on electoral support for the incumbent by utilising the introduction of the “Towns Fund” in England in 2019 as a natural experiment. For causal identification, I leverage a difference-in-difference design to examine the electoral effect of this fund. My findings suggest that providing funding to constituencies significantly increased the vote share of the Conservative Party in the General Election in 2019. However, in a subset of constituencies in which the Labour Party constitutes the incumbent, the findings can not be replicated for all specifications and robustness checks. Furthermore, I do not find consistent support that the effect is stronger in economically deprived constituencies. Similarly, the results suggest that the voting outcome depends on the total amount of funding being received, however, this finding does not reach statistical significance. These results complement the literature by providing empirical evidence for pork barrel as a functioning means for vote buying for the Conservative government in 2019 in England. Furthermore, this paper emphasises that partisanship should be considered as a mediating variable when analysing the political effect of providing place-based funding.
Keywords: 330; Political economy; Towns fund; Voting behaviour; Natural experiment; difference-in-difference; Funding